Factors Affecting Administrative Effectiveness in Experiential Learning Activities in General Education Institutions in Vietnam - Thuy, Pham Bich (Journal of Posthumanism, 2025)
This research aims to identify factors affecting the administrative effectiveness of experiential learning activities in general education institutions in Vietnam. Utilizing mixed research methods including qualitative method and survey of 451 management and teaching staff nationwide. The findings reveal that there are five major factors affecting the administrative effectiveness: leadership, support policies, teachers’ engagement, relationships with communities and resources for deployment. SEM analysis shows that leadership and support policies have the strongest impacts. On that basis, the author has proposed several policy recommendations to improve the administrative effectiveness of experiential learning activities in general education institutions. To be more specific, it is necessary to (1) enhance leadership and educational governance capabilities of principals, (2) issue certain policies to support experiential learning in the main educational programs, (3) promote teacher training in experiential learning activity organization, (4) develop collaborative mechanism between schools and social organizations, and (5) invest in proper facilities to ensure effectiveness in experiential activity deployment.